INITIAL-STAGES OF EPITAXIAL COSI(2) FORMATION ON SI(100) SURFACES - Fauster, Thomas; et al. (Physical Review B, 1994)
The initial stages of the CoSi2 formation on Si(100) surfaces after room-temperature Co deposition and subsequent annealing were studied using Auger electron spectroscopy, low-energy electron diffraction, and valence-band and core-level photoemission spectroscopy with synchrotron radiation. CoSi2 formation does not take place at room temperature. A coverage dependence of the reaction temperature on Si(100) is observed which is attributed to a change of the Co adsorption sites at room temperature above a Co coverage of approximately 2.5 monolayer. This is related to the formation of CoSi2 grains and of pinholes. Co-rich and Si-rich CoSi2 surfaces were observed and characterized for different annealing temperatures. A Si termination of the Co-rich surface is inferred from our data. A c(4x4) reconstruction of the Si-rich surface is observed.